A review of trends and adoption model for grid information technology. (21st November 2007) - Maqueira, J.M.; Bruque, S.
Nowadays, scientific projects require collaborative environments and powerful computing resources capable of handling huge quantities of data, which gives rise to e-science. These requirements are evident in the need to optimise time and efforts in activities having to do with health and biotechnology. Scientists are taking increasing interest in an emerging technology ? Grid Information Technology (GRIT) ? that may offer a solution to their current needs. The current work aims to survey how GRIT is being used in the three main economic areas in the world: Europe, Asia-Pacific and the USA. Furthermore, we propose an adoption model of GRIT that may be applied to new health/biotechnology research fields. The paper ends with a discussion on future directions and policy recommendations.